Cocaine Production And Trafficking : What Do We Know ? - Mejía, Daniel, 1975- 01.03.1975- (The World Bank, 2008)
The main purpose of this paper is to summarize the information currently available on cocaine production and trafficking. The paper starts by describing the available data on cocaine production and trade, the collection methodologies (if available) used by different sources, the main biases in the data, and the accuracy of different data sources. Next, it states some of the key empirical questions and hypotheses regarding cocaine production and trade and takes a first look at how well the data match these hypotheses. The paper states some of the main puzzles in the cocaine market and studies some of the possible explanations. These puzzles and empirical questions should guide future research on the key determinants of illicit drug production and trafficking. Finally, the paper studies the different policies that producer countries have adopted to fight against cocaine production and the role consumer countries play in the implementation of anti-drug policies